The emergence of xenophobic self within the contemporary Greek social experience: Findings based on focus groups - Ζήση, Αναστασία; Χτουρής, Σωτήρης; Χίου, Μιχαλίτσα; Ρενταρή, Μάλαμα (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The present paper provides a theoretical discussion of the qualitative findings generated by 14 focus groups conducted as a means to study phenomena of xenophobia and racism, individual and collective reactions of host majority members towards immigrants under the contemporary conditions of economic crisis that the country is facing. The focus groups were organized in order to examine how these social and economic conditions shape the ways host majority members and immigrants coexist, their daily experiences, the type and quality of intergroup relations. Content analysis was focused on the host society members’ lines of arguments, beliefs and perceptions that they developed on issues related to immigrants and immigration. The analysis revealed four different themes; a) xenophobia as negation and rejection of the foreigners, b) xenophobia as a reaction that derives from the idea of the “indigenous citizen” who is entitled to his/her resources, c) xenophobia as an ambivalent reaction, and d) the political production of xenophobia. The contemporary conditions of the country characterized by structural violence contribute in the emergence of a new type struggling xenophobic self as a generator of a negative dialectic relationship between an individual xenophobic reaction and a collective one.